Species Diversity of Ramphogordius sanguineus/Lineus ruber -Like Nemerteans (Nemertea: Heteronemertea) and Geographic Distribution of R. sanguineus - Kang, Xing Xing (2015)
Heteronemerteans, such as Lineus ruber, L. viridis, Ramphogordius sanguineus, R. lacteus, Riseriellus occultus, and Micrura varicolor, share many similar external characters. Although several internal characters useful for distinguishing these nemertean species have been documented, their identification is based mostly on coloration, the shape of the head, and how they contract, which may not be always reliable. We sequenced the mitochondrial COI gene for 160 specimens recently collected from 27 locations around the world (provisionally identified as the above species, according to external characters and contraction patterns, with most of them as R. sanguineus). Based on these specimens, together with sequences of 16 specimens from GenBank, we conducted a DNA-based species delimitation/identification by means of statistical parsimony and phylogenetic analyses. Our results show that the analyzed specimens may contain nine species, which can be separated by large genetic gaps; heteronemerteans with an external appearance similar to R. sanguineus/Lineus ruber/L. viridis have high species diversity in European waters from where eight species can be discriminated. Our 42 individuals from Vancouver Island (Canada) are revealed to be R. sanguineus, which supports an earlier argument that nemerteans reported as L. ruber or L. viridis from the Pacific Northwest may refer to this species. We report R. sanguineus from Chile, southern China, and the species is also distributed on the Atlantic coast of South America (Argentina). In addition, present analyses reveal the occurrence of L. viridis in Qingdao, which is the first record of the species from Chinese waters.